2017
DOI: 10.1093/mnras/stx3143
|View full text |Cite
|
Sign up to set email alerts
|

The impact of galactic disc environment on star-forming clouds

Abstract: We explore the effect of different galactic disc environments on the properties of starforming clouds through variations in the background potential in a set of isolated galaxy simulations. Rising, falling and flat rotation curves expected in halo dominated, disc dominated and Milky Way-like galaxies were considered, with and without an additional two-arm spiral potential. The evolution of each disc displayed notable variations that are attributed to different regimes of stability, determined by shear and grav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 117 publications
2
16
1
Order By: Relevance
“…If we assume our model is correct, then we can interpret the relative differences in σ − L relations between differing spiral galaxies as due to differences in the strength of spiral shocks, at least where they interact with molecular gas (cf Nguyen et al 2018). More explicitly, the spiral shocks of NGC 4526 must be weaker than those of the Milky Way to be consistent with the model.…”
Section: Discussionmentioning
confidence: 99%
“…If we assume our model is correct, then we can interpret the relative differences in σ − L relations between differing spiral galaxies as due to differences in the strength of spiral shocks, at least where they interact with molecular gas (cf Nguyen et al 2018). More explicitly, the spiral shocks of NGC 4526 must be weaker than those of the Milky Way to be consistent with the model.…”
Section: Discussionmentioning
confidence: 99%
“…Exactly how clouds depend on the non-axisymmetric spiral structure has been the subject of only a few studies. Nguyen et al (2018) found E-mail: alex@astro1.sci.hokudai.ac.jp that the impact of spiral features vastly exceeds changes possible from differing rotation curves (i.e. differing shear rates).…”
Section: Introductionmentioning
confidence: 99%
“…They also observe a population of unbound objects that are typically observed as a product of cloud interactions in dense filamentary structures. Similarly, Nguyen et al (2018) find that simulations that include spiral perturbation tend to generate a high degree of agglomeration of clouds within the spiral arms, with a general decrease in the number of small and medium-sized objects (with masses < 10 6 M ) in the disc, together with an incremental increase in the size of the unbound population. Cloud properties do not appear to be strongly influenced by the kind of spiral perturbation (flocculent, granddesign, or perturbed by a companion iteration), as shown by Pettitt et al (2020), who nevertheless found that the cloud mass spectra and contrast between arms and inter-arm regions di↵er depending on the type of spiral arms.…”
Section: Introductionmentioning
confidence: 78%